The interplay between prolactin and cardiovascular disease - Glezer, Andrea; Santana, Mariana Ramos; Bronstein, Marcello D.; Donato, Jose; Jallad, Raquel Soares (Frontiers in Endocrinology, 2023)
Hyperprolactinemia can be caused by several conditions and its effects on the hypothalamic-pituitary-gonadal axis are understood in more detail. Nevertheless, in recent decades, other metabolic effects have been studied and data pointed to a potential increased cardiovascular disease (CVD) risk. A recent study showed a decrease in total and LDL- cholesterol only in men with prolactinoma treated with dopamine agonists (DA) supporting the previous results of a population study with increased CVD risk in men harboring prolactinoma. However, other population studies did not find a correlation between prolactin (PRL) levels and CVD risk or mortality. There is also data pointing to an increase in high-density lipoprotein levels, and decreases in triglycerides, carotid-intima-media thickness, C-reactive protein, and homocysteine levels in patients with prolactinoma on DA treatment. PRL was also implicated in endothelial dysfunction in pre and postmenopausal women. Withdrawal of DA resulted in negative changes in vascular parameters and an increase in plasma fibrinogen. It has been shown that PRL levels were positively correlated with blood pressure and inversely correlated with dilatation of the brachial artery and insulin sensitivity, increased homocysteine levels, and elevated D-dimer levels. Regarding possible mechanisms for the association between hyperprolactinemia and CVD risk, they include a possible direct effect of PRL, hypogonadism, and even effects of DA treatment, independently of changes in PRL levels. In conclusion, hyperprolactinemia seems to be associated with impaired endothelial function and DA treatment could improve CVD risk. More studies evaluating CVD risk in hyperprolactinemic patients are important to define a potential indication of treatment beyond hypogonadism.